Analysis and Testing of Load Characteristics for Rotary-Percussive Drilling of Lunar Rock Simulant with a Lunar Regolith Coring Bit. (30th April 2017) - Li, Peng; Zhang, Hui; Jiang, Shengyuan; Zhang, Weiwei
Abstract : Based on an optimized lunar regolith coring bit (LRCB) configuration, the load characteristics of rotary-percussive drilling of lunar rock simulant in a laboratory environment are analyzed to determine the effects of the drilling parameters (the rotational velocity, the penetration rate, and the percussion frequency) on the drilling load. The process of rotary drilling into lunar rock using an LRCB is modeled as an interaction between an elemental blade and the rock. The rock's fracture mechanism during different stages of the percussive mechanism is analyzed to create a load forecasting model for the cutting and percussive fracturing of rock using an elemental blade. Finally, a model of the load on the LRCB is obtained from the analytic equation for the bit's cutting blade distribution; experimental verification of the rotary-impact load characteristics for lunar rock simulant with different parameters is performed. The results show that the penetrations per revolution (PPR) are the primary parameter influencing the drilling load. When the PPR are fixed, increasing the percussion frequency reduces the drilling load on the rock. Additionally, the variation pattern of the drilling load of the bit is in agreement with that predicted by the theoretical model. This provides a research basis for subsequent optimization of the drilling procedure and online recognition of the drilling process.